Brain atrophy in middle age using magnetic resonance imaging scans from Japan's health screening programme. Issue 4 (22nd August 2022) - Mori, Susumu; Onda, Kengo; Fujita, Shohei; Suzuki, Toshiaki; Ikeda, Mikimasa; Zay Yar Myint, Khin; Hikage, Jun; Abe, Osamu; Tomimoto, Hidekazu; Oishi, Kenichi; Taguchi, Junichi
Abstract: Although health screening plays a key role in the management of chronic diseases associated with lifestyle choices, brain health is not generally monitored, remaining a black box prior to the manifestation of clinical symptoms. Japan is unique in this regard, as brain MRI scans have been widely performed for more than two decades as part of Brain Dock, a comprehensive health screening programme. A vast number of stored images (well over a million) of longitudinal scans and extensive health data are available, offering a valuable resource for investigating the prevalence of various types of brain-related health conditions occurring throughout adulthood. In this paper, we report on the findings of our preliminary quantitative analysis of T1 -weighted MRIs of the brain obtained from 13 980 subjects from three participating sites during the period 2015–19. We applied automated segmentation analysis and observed age-dependent volume loss of various brain structures. We subsequently investigated the effects of scan protocols and the feasibility of calibration for pooling the data. Last, the degree of brain atrophy was correlated with four known risk factors of dementia; blood glucose level, hypertension, obesity, and alcohol consumption. In this initial analysis, we identified brain ventricular volume as an effective marker of age-dependent brain atrophy, being highly sensitive to ageing and evidencing strong robustness against protocol variability. We established the normal range of ventricular volumes at each age, which is an essential first step for establishing criteria used to interpret data obtained for individual participants. We identified a subgroup of individuals at midlife with ventricles that substantially exceeded the average size. The correlation studies revealed that all four risk factors were associated with greater ventricular volumes at midlife, some of which reached highly significant sizes. This study demonstrates the feasibility of conducting a large-scale quantitative analysis of existing Brain Dock data in Japan. It will importantly guide future efforts to investigate the prevalence of large ventricles at midlife and the potential reduction of this prevalence, and hence of dementia risk, through lifestyle changes. Abstract : Mori et al . investigated midlife brain atrophy and its association with lifestyle using a large MRI data repository in Japan. Ventricular volumes were highly sensitive to ageing and remain robust against protocol variability. The study found significant correlations between ventricular volumes and four known modifiable risk factors of dementia. Graphical Abstract: Graphical Abstract